If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -1g) + -3(2g + -6) = 8(3g + -1) + -11(g + -5) (4 * 2 + -1g * 2) + -3(2g + -6) = 8(3g + -1) + -11(g + -5) (8 + -2g) + -3(2g + -6) = 8(3g + -1) + -11(g + -5) Reorder the terms: 8 + -2g + -3(-6 + 2g) = 8(3g + -1) + -11(g + -5) 8 + -2g + (-6 * -3 + 2g * -3) = 8(3g + -1) + -11(g + -5) 8 + -2g + (18 + -6g) = 8(3g + -1) + -11(g + -5) Reorder the terms: 8 + 18 + -2g + -6g = 8(3g + -1) + -11(g + -5) Combine like terms: 8 + 18 = 26 26 + -2g + -6g = 8(3g + -1) + -11(g + -5) Combine like terms: -2g + -6g = -8g 26 + -8g = 8(3g + -1) + -11(g + -5) Reorder the terms: 26 + -8g = 8(-1 + 3g) + -11(g + -5) 26 + -8g = (-1 * 8 + 3g * 8) + -11(g + -5) 26 + -8g = (-8 + 24g) + -11(g + -5) Reorder the terms: 26 + -8g = -8 + 24g + -11(-5 + g) 26 + -8g = -8 + 24g + (-5 * -11 + g * -11) 26 + -8g = -8 + 24g + (55 + -11g) Reorder the terms: 26 + -8g = -8 + 55 + 24g + -11g Combine like terms: -8 + 55 = 47 26 + -8g = 47 + 24g + -11g Combine like terms: 24g + -11g = 13g 26 + -8g = 47 + 13g Solving 26 + -8g = 47 + 13g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-13g' to each side of the equation. 26 + -8g + -13g = 47 + 13g + -13g Combine like terms: -8g + -13g = -21g 26 + -21g = 47 + 13g + -13g Combine like terms: 13g + -13g = 0 26 + -21g = 47 + 0 26 + -21g = 47 Add '-26' to each side of the equation. 26 + -26 + -21g = 47 + -26 Combine like terms: 26 + -26 = 0 0 + -21g = 47 + -26 -21g = 47 + -26 Combine like terms: 47 + -26 = 21 -21g = 21 Divide each side by '-21'. g = -1 Simplifying g = -1
| 4x+5y=2470 | | Y=cot(7x) | | 14+5n=14+3n | | x^2y+y^2x=14040 | | 2u+9=45 | | c=(a-u)/n | | ac=mc+n | | 12w^2+9w^3=0 | | 16-h^2+6hy+9y^2= | | x=(y-q)/m | | x=315/80 | | 315/80 | | X^3-3x-4x+12=0 | | -4+5+m=-3+7 | | -47+5+y=-2+4 | | 3y^2-22y+32=0 | | 7y-6y-4=5 | | 5x^2+45x-10=0 | | 7-1-(18-2)/8 | | 3y^2-22y-32=0 | | -1=3x^2-8x | | 2(x+1)+x=62 | | 1.32y+0.02=1.19+y | | -2(z+4)=-32 | | f(t)=-16-64t+80 | | (2x-1)(2x-1)(2x-1)= | | 6x+7=4-(9x-5) | | 2(x-3)+2=-2 | | (4x-2)(3x+5)= | | -4w=16 | | 228=2(2w-9)+2w | | 3(4x+2)=19 |